Filtration Behavior and Solid–Liquid Separation Mechanisms in an Integrated Electrocoagulation–Filtration–Chelation System for Heavy Metal Removal from Laboratory Wastewater - Rasul Cafarov; Hameda Hameda; Rahayu Yuliastri Fadhilah; Emmanouil Konstantinidis (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to investigate the filtration behavior and solid–liquid separation mechanisms in an integrated electrocoagulation–filtration–chelation system for treating highly contaminated laboratory wastewater, with emphasis on the role of filtration as the main separation unit controlling overall treatment performance. Methodology: Electrocoagulation was conducted using aluminum electrodes in a batch reactor, followed by gravity-driven filtration using cellulose filter media and chelation using tamarind extract. Heavy metals were analyzed using Atomic Absorption Spectroscopy (AAS, Shimadzu AA-7000). COD was measured using standard dichromate method. Filtration behavior was interpreted using classical Darcy’s law. Main Findings: The integrated system achieved significant removal of heavy metals, with mercury reduced to 0.001 ppm, cadmium to 0.002 ppm, and lead to 0.123 ppm. COD was also substantially decreased. Filtration exhibited cake formation behavior, where floc accumulation increased resistance and reduced flux over time, while improving solid–liquid separation efficiency. Novelty/Originality of this study: This study introduces a filtration-centered perspective in an integrated electrocoagulation–filtration–chelation system by emphasizing cake filtration mechanisms and resistance-controlled behavior. It advances existing knowledge by linking physicochemical transformation with mechanical separation, demonstrating how phase conversion enhances filterability and overall separation efficiency in wastewater treatment systems.